The Role of Personal Evangelization School in the Suffragan Diocese of Bogor in Fostering Lay Apostolate Spirituality in the Digital Era - Yanto Sandy Tjang; Felisitas Yuswanto; Florensius Sutami; Mayong Andreas Acin; Laurentius Prasetyo; Laurencia Müller (Studia Philosophica et Theologica, 2026)
The study explores the role of the Personal Evangelization School (PES) as a structured model of lay formation in fostering apostolate spirituality within the contemporary Church, particularly in the Indonesian context and the digital era. Rooted in the ecclesiology of the Second Vatican Council, the study responds to challenges such as secularization, limited lay formation, and the expansion of digital culture. Using a qualitative descriptive approach based on literature review and supported by observational data from PES activities in the Suffragan Diocese of Bogor, the study analyzes the theological foundations and pastoral practices of PES. The findings show that PES effectively cultivates lay apostolate spirituality by integrating personal encounter with Christ, communal participation, and missionary engagement. A key contribution of the study lies in demonstrating how digital platforms, such as Zoom, reshape the nature of ―personal encounter‖ through mediated, dialogical, and reflective interactions. While these digital encounters foster authentic forms of communion, They remain distinct from the embodied presence required in sacramental life. In conclusion, PES emerges as a strategic pastoral instrument that bridges theological reflection and pastoral praxis, forming missionary disciples capable of engaging both physical and digital spaces.